Core-shell type submicron silicon-based negative electrode material and preparation method thereof, lithium ion battery and electric equipment
By using core-shell submicron silicon-based anode material in lithium-ion batteries, the multi-layer structure is used to alleviate the volume changes of silicon particles, and the problem of rapid attenuation of battery capacity and life caused by volume changes in silicon in lithium-ion batteries is solved, and the problem of rapid attenuation of battery capacity and life due to volume changes in lithium-ion batteries is achieved. Higher energy density and longer cycle life.
Patent Information
- Application Number
- CN202411666212.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-14
AI Technical Summary
Silicon will undergo significant volume changes during the lithiation and delithiation of lithium-ion batteries, resulting in structural breakage, electrical disconnection and unstable phase layer growth of solid electrolytes, thereby rapidly attenuating the battery capacity and life.
A core-shell submicron silicon-based anode material is used, including the core being submicron silicon, the first cladding layer is a plurality of graphene sheets and carbon fillers, and the second cladding layer is hard carbon. Through vapor phase carbon deposition coating treatment, the use of carbonyl polymers and phenolic resin alcohol solutions, a multilayer structure is formed to alleviate volume expansion and improve electrochemical cycle stability.
It improves the energy density and cycle stability of lithium-ion batteries, enhances the anti-expansion ability and conductivity, and extends the cycle life of the battery.
Smart Images

Figure CN119447260A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of negative electrode materials for lithium-ion batteries, and in particular to a core-shell submicron silicon-based negative electrode material and a preparation method thereof, a lithium-ion battery and electrical equipment. Background Art
[0002] With the rapid expansion of the energy storage market (electric vehicles and portable electronic devices), there is a huge demand for high-performance lithium-ion batteries with high energy density and long cycle life. Based on the above needs, there is an urgent need to develop high-capacity negative electrode materials with stable cycle characteristics; among them, silicon has the advantages of ultra-high theoretical capacity (4200mAh / g, Li4.4Si), suitable operating voltage (relative to Li+ / Li~0.5V) and abundant reserves, so it can be used as a viable alternative negative electrode material for graphite negative electrodes of lithium-ion batteries.
[0003] However, in actual electrochemical applications, silicon undergoes a significant volume change of about 300% during lithiation and delithiation. This huge volume shrinkage can lead to particle structure fragmentation, electrical disconnection between particles, and the growth of unstable solid electrolyte interphase layers, resulting in rapid decay of battery capacity and life.
[0004] In addition, the poor electrical conductivity of silicon also greatly inhibits its charge and discharge behavior. Although adjusting the particle size of silicon from micrometers to nanometers can effectively shorten the diffusion path of lithium ions and reduce the expansion and pulverization of silicon particles, thereby improving its lithium storage kinetics and cycle stability, nano-sized silicon particles are very easy to agglomerate, and the large specific surface area of nano-silicon makes it easy to react with the electrolyte at the solid-liquid interface, resulting in capacity loss.
[0005] Therefore, how to prepare negative electrode materials that can effectively alleviate the volume expansion of silicon particles and improve the electrochemical cycle life of batteries is an urgent problem that needs to be solved. Summary of the invention
[0006] The purpose of the present application is to provide a core-shell submicron silicon-based negative electrode material and a preparation method thereof, a lithium-ion battery and an electrical device to solve the above-mentioned problems.
[0007] To achieve the above objectives, the present application provides a core-shell submicron silicon-based negative electrode material in a first aspect, comprising a core, a first coating layer, and a second coating layer;
[0008] The first coating layer covers the core, and the second coating layer covers the first coating layer;
[0009] The core includes submicron silicon, the first coating layer includes a plurality of graphene sheets contacting the surface of the core and discontinuous or continuous carbon fillers filled in gaps between the plurality of graphene sheets, and the second coating layer includes hard carbon.
[0010] Optionally, the core-shell submicron silicon-based negative electrode material meets at least one of the following conditions:
[0011] A. The raw material of the carbon filler includes a carbonyl polymer;
[0012] B. the raw material of the hard carbon comprises a phenolic resin alcohol solution;
[0013] C. The particle size of the core is 0.3 μm-1 μm;
[0014] D. The thickness of the first coating layer is 0.3 μm-2 μm;
[0015] E. The thickness of the second coating layer is 3 μm-14 μm.
[0016] Optionally, the core-shell submicron silicon-based negative electrode material meets at least one of the following conditions:
[0017] A. the carbonyl polymer comprises one or more of nonionic polyacrylamide, polyamide-amine, polyacrylic acid, and polylactic acid-glycolic acid copolymer;
[0018] B. the phenolic resin alcohol solution comprises a phenolic resin ethylene glycol solution;
[0019] C. The solid content of the phenolic resin alcohol solution is 2%-8%.
[0020] The second aspect of the present application provides a method for preparing the core-shell submicron silicon-based negative electrode material, comprising:
[0021] Under a protective atmosphere, the submicron silicon powder is subjected to a first heating and vapor phase carbon deposition coating treatment to obtain a product A;
[0022] The product A and the carbonyl polymer are first mixed and ground to obtain a product B;
[0023] The product B and the phenolic resin alcohol solution are subjected to a second mixing, solid-liquid separation, and a second heating to obtain a core-shell type submicron silicon-based negative electrode material.
[0024] Optionally, the method for preparing the core-shell submicron silicon-based negative electrode material satisfies at least one of the following conditions:
[0025] A. The protective gas in the protective atmosphere includes argon;
[0026] B. The purity of the submicron silicon powder is greater than or equal to 80%;
[0027] C. The mass ratio of the product A to the carbonyl polymer is 3:0.5-3;
[0028] D. The mass ratio of the product B to the phenolic resin alcohol solution is 1:5-20.
[0029] Optionally, the method for preparing the core-shell submicron silicon-based negative electrode material satisfies at least one of the following conditions:
[0030] A. The vapor phase carbon deposition coating process comprises: introducing hydrogen and acetylene to react;
[0031] B. The grinding time is 30min-120min;
[0032] C. the grinding comprises ball milling;
[0033] D. Before the second heating, the mixture obtained by the second mixing is allowed to stand.
[0034] Optionally, the method for preparing the core-shell submicron silicon-based negative electrode material satisfies at least one of the following conditions:
[0035] A. The reaction time is 0.5h-2h;
[0036] B. The gas flow rate of the hydrogen is 60mL / min-120mL / min;
[0037] C. The gas flow rate of the acetylene is 10mL / min-30mL / min;
[0038] D. The standing time is 1h-4h.
[0039] Optionally, the method for preparing the core-shell submicron silicon-based negative electrode material satisfies at least one of the following conditions:
[0040] A. The heating rate of the first heating is 3°C / min-6°C / min, and the heating end temperature is 900°C-1200°C;
[0041] B. the second heating includes a third heating and a fourth heating performed sequentially;
[0042] The third heating has a heating rate of 3°C / min-6°C / min, a heating end point temperature of 400°C-650°C, and a heating time of 1h-3h;
[0043] The fourth heating has a heating rate of 3°C / min-6°C / min, a heating end point temperature of 900°C-1100°C, and a heating time of 3h-6h.
[0044] A third aspect of the present application provides a lithium-ion battery, comprising the core-shell submicron silicon-based negative electrode material or the core-shell submicron silicon-based negative electrode material prepared by the method for preparing the core-shell submicron silicon-based negative electrode material.
[0045] A fourth aspect of the present application provides an electrical device comprising the lithium-ion battery.
[0046] Compared with the prior art, the beneficial effects of this application include:
[0047] The core-shell submicron silicon-based negative electrode material provided by the present application, firstly, the core is submicron silicon, which has a higher compaction density and is more conducive to the improvement of the energy density of the battery core, and has better anti-expansion ability and electrochemical activity than micron silicon; secondly, the multiple graphene sheets in the first coating layer that are in contact with the surface of the core can not only reduce the stress concentration on the first coating layer, but also transfer the stress generated during the rolling of the pole piece from the second coating layer to the graphene sheets, thereby reducing the stress concentration on the first coating layer, which is helpful to withstand a larger electrode rolling force from the micromechanical structure, and the two ends of the multiple highly conductive graphene sheets connect the core and the second coating layer to form a core and the first coating layer. The direct electrical connection path between the two coating layers establishes more lithium ion diffusion pathways, which helps to promote the rapid transmission of lithium ions, thereby improving the conductivity of the core-shell submicron silicon-based negative electrode material; then, the carbon filler in the first coating layer not only creates gap space inside the core-shell submicron silicon-based negative electrode material to alleviate the volume expansion during the silicon lithiation process, but also the carbon filler and the second coating layer are connected through hydroxyl-carbonyl groups, making the first coating layer and the second coating layer more closely connected; finally, the second coating layer can not only further improve the conductivity of the silicon-based material, but also effectively alleviate the large volume expansion / contraction effect of the core-shell submicron silicon-based negative electrode material. The core-shell submicron silicon-based negative electrode material has excellent anti-expansion ability and cycle stability.
[0048] The present application provides a method for preparing a core-shell submicron silicon-based negative electrode material, which uses vapor phase carbon deposition coating treatment to obtain multiple graphene sheets perpendicular to the inner core, and then introduces a carbonyl polymer into the pores between the multiple graphene sheets. The hydroxyl groups in the phenolic resin alcohol solution and the carbonyl polymer rich in carbonyl (C=O) in the pores of the graphene sheets are self-assembled by hydroxyl-carbonyl groups to achieve uniform adsorption of the phenolic resin alcohol solution. The phenolic resin alcohol solution adsorbed on the carbonyl polymer and the graphene sheets is deposited and coated by its own hydrogen bonding. The carbonyl polymer with a lower residual carbon content is decomposed by a second heating to create space inside the first coating layer, while the phenolic resin alcohol solution with a higher residual carbon content forms a dense carbon shell.
[0049] The lithium-ion battery and electrical equipment provided by the present application have high capacity and long cycle life. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0051] Figure 1 Schematic diagram of the preparation process of core-shell submicron silicon-based negative electrode materials;
[0052] Figure 2 This is a SEM image of the micron-sized silicon-based material provided in Example 1;
[0053] Figure 3 is a SEM image of the submicron silicon powder in Example 1;
[0054] Figure 4 This is a SEM image of the core-shell submicron silicon-based negative electrode material prepared in Example 1;
[0055] Figure 5 This is an electrochemical cycle test curve diagram of the lithium-ion battery provided in Example 1. DETAILED DESCRIPTION
[0056] As used herein:
[0057] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0058] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0059] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0060] In these examples, parts and percentages are by mass unless otherwise indicated.
[0061] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0062] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0063] The first aspect of the present application provides a core-shell submicron silicon-based negative electrode material, comprising a core, a first coating layer, and a second coating layer;
[0064] The first coating layer covers the core, and the second coating layer covers the first coating layer;
[0065] The core includes submicron silicon, the first coating layer includes a plurality of graphene sheets contacting the surface of the core and discontinuous or continuous carbon fillers filled in gaps between the plurality of graphene sheets, and the second coating layer includes hard carbon.
[0066] It should be noted that one end of the plurality of graphene sheets is connected to the inner core, and the other end opposite thereto is connected to the second cladding layer, and some of the graphene sheets may be perpendicular to the inner core or the second cladding layer.
[0067] It is also worth noting that compared with amorphous carbon, ordered graphene layers occupy the non-lithium active gaps in the first coating layer structure, and their graphitic carbon framework can provide additional lithium storage space.
[0068] In some embodiments, the core-shell submicron silicon-based negative electrode material satisfies at least one of the following conditions:
[0069] A. The raw material of the carbon filler includes a carbonyl polymer;
[0070] B. the raw material of the hard carbon comprises a phenolic resin alcohol solution;
[0071] C. The particle size of the core is 0.3 μm-1 μm;
[0072] Optionally, the particle size of the core may be 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm or any value between 0.3 μm and 1 μm;
[0073] It should be noted that when the core particle size is 0.3μm-1μm, the comprehensive electrochemical performance of silicon-carbon materials is better. This is because when the core silicon particle size is greater than 1μm, silicon will cause more obvious volume expansion during continuous charge and discharge, which will lead to cracking of the pole piece, and the continuous consumption of electrolyte by the broken new cross section will also greatly reduce the cycle life of the battery cell. On the contrary, when the core silicon particle size is less than 0.3μm, the lower bulk density and larger specific surface area of the silicon-carbon material powder are not conducive to the improvement of the volume energy density of the battery cell, and will also lead to lower electrochemical charge and discharge coulomb efficiency;
[0074] D. The thickness of the first coating layer is 0.3 μm-2 μm;
[0075] Optionally, the thickness of the first coating layer may be 0.3 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm or any value between 0.3 μm and 2 μm;
[0076] E. The thickness of the second coating layer is 3 μm-14 μm.
[0077] Optionally, the thickness of the second coating layer may be 3 μm, 6 μm, 9 μm, 12 μm, 14 μm or any value between 3 μm and 14 μm.
[0078] In some embodiments, the core-shell submicron silicon-based negative electrode material satisfies at least one of the following conditions:
[0079] A. the carbonyl polymer comprises one or more of nonionic polyacrylamide, polyamide-amine, polyacrylic acid, and polylactic acid-glycolic acid copolymer;
[0080] It should be noted that the carbonyl polymer is used as the organic carbon source of the first coating layer, which is based on the fact that the carbonyl group can form intermolecular hydrogen bonds with the hydroxyl groups in the second-layer phenolic resin structure to enhance the inter-structural forces;
[0081] B. the phenolic resin alcohol solution comprises a phenolic resin ethylene glycol solution;
[0082] It should be noted that the phenolic resin ethylene glycol solution is used as the organic carbon source of the second coating layer. This is based on the fact that the hard carbon structure formed after the carbonization of the thermosetting phenolic resin has good conductivity and high strength, which can not only accelerate the electron / ion transmission but also effectively resist the volume change caused by the expansion of some silicon bases.
[0083] C. The solid content of the phenolic resin alcohol solution is 2%-8%.
[0084] Optionally, the solid content of the phenolic resin alcohol solution may be 2%, 3%, 4%, 5%, 6%, 7%, 8% or any value between 2% and 8%.
[0085] It should be noted that when the solid content in the phenolic resin alcohol solution is 2%-8%, the outer carbon structure coating thickness is appropriate and the comprehensive electrochemical performance of the silicon-carbon material is better. Too high carbon introduction will lead to a decrease in material capacity, but too low hard carbon content will reduce the conductivity and anti-expansion ability of the silicon-carbon material.
[0086] The second aspect of the present application provides a method for preparing the core-shell submicron silicon-based negative electrode material, comprising:
[0087] Under a protective atmosphere, the submicron silicon powder is subjected to a first heating and vapor phase carbon deposition coating treatment to obtain a product A;
[0088] It should be noted that the submicron silicon powder is first heated under a protective atmosphere, which not only decomposes the impurities inside it, but also makes the heating under a protective atmosphere safer. After the first heating is paused, the gas phase is introduced to deposit carbon on the surface of the submicron silicon, thereby forming a graphene sheet that contacts the surface of the submicron silicon powder.
[0089] The product A and the carbonyl polymer are first mixed and ground to obtain a product B;
[0090] The product B and the phenolic resin alcohol solution are subjected to a second mixing, solid-liquid separation, and a second heating to obtain a core-shell type submicron silicon-based negative electrode material.
[0091] The preparation process of the core-shell submicron silicon-based negative electrode material is shown in the figure below: Figure 1 shown.
[0092] In some embodiments, the method for preparing the core-shell submicron silicon-based negative electrode material satisfies at least one of the following conditions:
[0093] A. The protective gas in the protective atmosphere includes argon;
[0094] B. The purity of the submicron silicon powder is greater than or equal to 80%;
[0095] Optionally, the purity of the submicron silicon powder may be 80%, 85%, 90%, 95%, 99%, 99.9%, 99.99%, 99.999% or any value greater than or equal to 80%;
[0096] It should be noted that in the first heating process, high-temperature carbonization will evaporate and remove the solvent substances in the silicon base, and also carbonize most of the non-metallic impurities to form conductive carbon materials;
[0097] C. The mass ratio of the product A to the carbonyl polymer is 3:0.5-3;
[0098] Optionally, the mass ratio of product A to carbonyl polymer may be 3:0.5, 3:1, 3:2, 3:3 or any value between 3:0.5 and 3;
[0099] D. The mass ratio of the product B to the phenolic resin alcohol solution is 1:5-20.
[0100] Optionally, the mass ratio of product B to the phenolic resin alcohol solution can be 1:5, 1:10, 1:15, 1:20 or any value between 1:5-20.
[0101] In some embodiments, the method for preparing the core-shell submicron silicon-based negative electrode material satisfies at least one of the following conditions:
[0102] A. The vapor phase carbon deposition coating process comprises: introducing hydrogen and acetylene to react;
[0103] It should be noted that the multiple graphene sheets that are in contact with the surface of the core obtained by the gas phase carbon deposition coating process need to pass through a reducing gas. The introduction of the reducing gas can prevent the partial oxidation of the carbon material during the carbonization process to form defects and vacancies, which will lead to uneven lithium ion deposition during the subsequent charge and discharge process.
[0104] B. The grinding time is 30min-120min;
[0105] Optionally, the grinding time can be 30 min, 60 min, 90 min, 120 min or any value between 30 min and 120 min;
[0106] C. the grinding comprises ball milling;
[0107] D. Before the second heating, the mixture obtained by the second mixing is allowed to stand.
[0108] In some embodiments, the method for preparing the core-shell submicron silicon-based negative electrode material satisfies at least one of the following conditions:
[0109] A. The reaction time is 0.5h-2h;
[0110] Optionally, the reaction time can be 0.5h, 1h, 1.5h, 2h or any value between 0.5h and 2h;
[0111] B. The gas flow rate of the hydrogen is 60mL / min-120mL / min;
[0112] Optionally, the gas flow rate of hydrogen can be 60 mL / min, 80 mL / min, 100 mL / min, 120 mL / min, or any value between 60 mL / min and 120 mL / min;
[0113] C. The gas flow rate of the acetylene is 10mL / min-30mL / min;
[0114] Optionally, the gas flow rate of acetylene can be 10 mL / min, 20 mL / min, 30 mL / min, or any value between 10 mL / min and 30 mL / min;
[0115] It should be noted that the flow rate of the reducing gas must be greater than the flow rate of the carbon source gas, which will effectively control the carbon deposition efficiency and coating structure morphology on the silicon substrate surface;
[0116] D. The standing time is 1h-4h.
[0117] Optionally, the standing time can be 1 h, 2 h, 3 h, 4 h or any value between 1 h and 4 h.
[0118] In some embodiments, the method for preparing the core-shell submicron silicon-based negative electrode material satisfies at least one of the following conditions:
[0119] A. The heating rate of the first heating is 3°C / min-6°C / min, and the heating end temperature is 900°C-1200°C;
[0120] Optionally, the heating rate of the first heating may be 3°C / min, 4°C / min, 5°C / min, 6°C / min or any value between 3°C / min-6°C / min, and the heating end point temperature may be 900°C, 1000°C, 1100°C, 1200°C or any value between 900°C-1200°C;
[0121] B. the second heating includes a third heating and a fourth heating performed sequentially;
[0122] The third heating has a heating rate of 3°C / min-6°C / min, a heating end point temperature of 400°C-650°C, and a heating time of 1h-3h;
[0123] Optionally, the heating rate of the third heating may be 3°C / min, 4°C / min, 5°C / min, 6°C / min or any value between 3°C / min-6°C / min, the heating end point temperature may be 400°C, 450°C, 500°C, 550°C, 600°C, 650°C or any value between 400°C-650°C, and the time may be 1h, 2h, 3h or any value between 1h-3h;
[0124] The fourth heating has a heating rate of 3°C / min-6°C / min, a heating end point temperature of 900°C-1100°C, and a heating time of 3h-6h.
[0125] Optionally, the heating rate of the third heating can be 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min or any value between 3℃ / min-6℃ / min, the heating end temperature can be 900℃, 1000℃, 1100℃ or any value between 900℃-1100℃, and the time can be 1h, 2h, 3h or any value between 1h-3h.
[0126] It should be noted that the second heating setting is a two-step graded heating. First, a low-temperature heating treatment is performed to prevent the rapid decomposition of linear organic polymers such as carbonyl polymers, which leads to the formation of a large number of voids inside the material and the reduction of the density of the carbon layer, and then a high-temperature heating is performed. A graded carbonization process is used to achieve direct contact between the graphene sheet and the carbon shell of the second coating layer, thereby establishing direct electrical contact between the inner core silicon and the carbon shell of the second coating layer.
[0127] A third aspect of the present application provides a lithium-ion battery, comprising the core-shell submicron silicon-based negative electrode material or the core-shell submicron silicon-based negative electrode material prepared by the method for preparing the core-shell submicron silicon-based negative electrode material.
[0128] A fourth aspect of the present application provides an electrical device comprising the lithium-ion battery.
[0129] It should be noted that electrical equipment may be but is not limited to mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc.; among them, mobile devices may include but are not limited to at least one of mobile phones, laptop computers, etc.; electric vehicles may include but are not limited to at least one of pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.
[0130] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0131] Example 1
[0132] In a first aspect, the present embodiment provides a core-shell submicron silicon-based negative electrode material, comprising a core, a first coating layer, and a second coating layer;
[0133] The first coating layer covers the inner core, the second coating layer covers the first coating layer, the inner core is submicron silicon, the first coating layer is a plurality of graphene sheets that abut against the inner core and discontinuous or continuous carbon fillers filled in the gaps between the plurality of graphene sheets, and the second coating layer is hard carbon;
[0134] The particle size of the inner core is 0.3 μm-1 μm, the thickness of the first coating layer is 1 μm, and the thickness of the second coating layer is 8 μm.
[0135] A second aspect of this embodiment provides a method for preparing a core-shell submicron silicon-based negative electrode material, comprising:
[0136] S1: After the micron-sized silicon-based material is crushed into powder by a sand mill coarse-to-fine grinding process, a screening classifier is used to screen out submicron-sized silicon powder with a particle size in the submicron size range of 0.3μm-1μm;
[0137] The scanning electron microscopy of the micron-scale silicon-based material Figure 2 As shown;
[0138] The scanning electron microscopy of the submicron silicon powder is as follows Figure 3 As shown;
[0139] S2: Submicron silicon powder was heated to 1000°C in an argon environment at a heating rate of 5°C / min, and then the atmosphere was switched to a mixed gas of hydrogen and acetylene (the gas flow rate of hydrogen was 110 mL / min, and the gas flow rate of acetylene was 25 mL / min) for heat treatment for 1.5 hours to prepare sSi@FDCs material;
[0140] S3: sSi@FDCs and carbonyl polymer nonionic polyacrylamide were put into a ball mill at a mass ratio of 3:2 and ball-milled at a speed of 300 rpm for 90 min;
[0141] S4: adding the mixture obtained in S3 to a 5% solid content phenolic resin ethylene glycol solution, the mass ratio of the mixture to the phenolic resin ethylene glycol solution being 1:10, stirring for 15 minutes and then standing for 120 minutes;
[0142] S5: After solid-liquid separation by centrifugation, the solid was dried at 200°C in a forced air oven for 8 h, then heated to 500°C at a rate of 5°C / min in an argon atmosphere, kept warm for 2 h, then heated to 1000°C and carbonized for 6 h to obtain sSi-C@PC-1 core-shell submicron silicon-based negative electrode material.
[0143] The scanning electron microscopy of the sSi-C@PC-1 core-shell submicron silicon-based negative electrode material is shown in Figure 4 shown.
[0144] A third aspect of the present embodiment provides a lithium-ion battery, wherein the core-shell type submicron silicon-based negative electrode material is coated on a copper foil to form a pole piece, wherein the silicon-based negative electrode material, conductive carbon, carbon nanotubes, and polyacrylic acid are prepared as a slurry by a high-speed disperser in a ratio of 82:10:1:7, the separator is PP2400, and a metal lithium sheet is used as a counter electrode to assemble into a 2032-type button battery.
[0145] The electrochemical cycle test curve of the lithium-ion battery is as follows: Figure 5 shown.
[0146] Example 2
[0147] The difference from Example 1 is that the carbonyl polymer is polyamide-amine.
[0148] Example 3
[0149] The difference from Example 1 is that the carbonyl polymer is polyacrylic acid.
[0150] Comparative Example 1
[0151] The difference from Example 1 is that the gas flow rate of acetylene is 3 mL / min.
[0152] Comparative Example 2
[0153] The difference from Example 1 is that in step S5, the temperature is lowered to 500° C. at a heating rate of 5° C. / min under an argon atmosphere, kept at that temperature for 0.5 h, and then raised to 1000° C. and carbonized for 2 h.
[0154] Comparative Example 3
[0155] The difference from Example 1 is that the particle size of the submicron silicon powder is larger than 1 μm and smaller than 2 μm.
[0156] Comparative Example 4
[0157] The difference from Example 1 is that the gas flow rate of acetylene is 40 mL / min.
[0158] Comparative Example 5
[0159] The difference from Example 1 is that the solid content of the phenolic resin ethylene glycol solution is 12%, and the standing time is 300 minutes.
[0160] Comparative Example 6
[0161] The difference from Example 1 is that in step S5, the temperature is lowered to 500° C. at a heating rate of 5° C. / min under an argon atmosphere, kept at that temperature for 4 h, and then raised to 1000° C. and carbonized for 8 h.
[0162] Comparative Example 7
[0163] The difference from Example 1 is that the first coating layer is hard carbon, and the second coating layer is a plurality of graphene sheets and discontinuous or continuous carbon fillers filled in the gaps between the plurality of graphene sheets.
[0164] Comparative Example 8
[0165] The difference from Example 1 is that no multiple graphene sheets in conflict with the inner core are provided, and the first coating layer is only a carbon layer whose raw material is carbonyl polymer non-ionic polyacrylamide.
[0166] Comparative Example 9
[0167] The difference from Example 1 is that in step S2, a mixed gas of hydrogen and acetylene is introduced while heating.
[0168] Comparative Example 10
[0169] The difference from Example 1 is that no second coating layer is provided.
[0170] Comparative Example 11
[0171] The difference from Example 1 is that the first coating layer is not provided.
[0172] Comparative Example 12
[0173] The difference from Example 1 is that during the preparation of the lithium-ion battery, the negative electrode active material is replaced with submicron silicon powder.
[0174] The lithium-ion batteries prepared in the above embodiments, comparative examples and control examples were subjected to electrochemical performance tests in a blue battery test system, with a voltage of 0.005-2V and a charge / discharge current of 0.5C / 0.5C. The specific tests included conductivity, specific capacity, first-cycle efficiency, number of cycles, capacity retention rate and electrode expansion rate. The results are shown in Table 1.
[0175] Table 1 Electrochemical performance test
[0176]
[0177] As can be seen from Table 1, the structural design of the present application can effectively improve the comprehensive electrochemical performance of submicron silicon-based materials, wherein the carbon connection network of the inner graphene sheet provides a fast ion / electron transmission path for the continuous lithiation / delithiation process, and the vertical graphene sheet on the silicon surface also helps to transfer the stress generated during the pole piece rolling process from the carbon shell to the graphene sheet, thereby reducing the stress concentration on the carbon shell. The hard carbon structure and appropriate carbon content of the outer layer will further effectively inhibit the volume expansion of the silicon base during the lithiation / delithiation process and reduce the pole piece expansion rate; the coordinated optimization of the inner and outer layer structures has a significant effect on improving the electrochemical cycle performance of submicron silicon-based materials.
[0178] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0179] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A core-shell submicron silicon-based negative electrode material, characterized in that: comprising a core, a first coating layer, and a second coating layer; The first coating layer covers the core, and the second coating layer covers the first coating layer; The core includes submicron silicon, the first coating layer includes a plurality of graphene sheets contacting the surface of the core and discontinuous or continuous carbon fillers filled in gaps between the plurality of graphene sheets, and the second coating layer includes hard carbon.
2. The core-shell submicron silicon-based negative electrode material according to claim 1, characterized in that: At least one of the following conditions is met: A. The raw material of the carbon filler includes a carbonyl polymer; B. the raw material of the hard carbon comprises a phenolic resin alcohol solution; C. The particle size of the core is 0.3 μm-1 μm; D. The thickness of the first coating layer is 0.3 μm-2 μm; E. The thickness of the second coating layer is 3 μm-14 μm.
3. The core-shell submicron silicon-based negative electrode material according to claim 2, characterized in that: At least one of the following conditions is met: A. the carbonyl polymer comprises one or more of nonionic polyacrylamide, polyamide-amine, polyacrylic acid, and polylactic acid-glycolic acid copolymer; B. the phenolic resin alcohol solution comprises a phenolic resin ethylene glycol solution; C. The solid content of the phenolic resin alcohol solution is 2%-8%.
4. A method for preparing a core-shell submicron silicon-based negative electrode material according to any one of claims 1 to 3, characterized in that: include: Under a protective atmosphere, the submicron silicon powder is subjected to a first heating and vapor phase carbon deposition coating treatment to obtain a product A; The product A and the carbonyl polymer are first mixed and ground to obtain a product B; The product B and the phenolic resin alcohol solution are subjected to a second mixing, solid-liquid separation, and a second heating to obtain a core-shell type submicron silicon-based negative electrode material.
5. The method for preparing a core-shell submicron silicon-based negative electrode material according to claim 4, characterized in that: At least one of the following conditions is met: A. The protective gas in the protective atmosphere includes argon; B. The purity of the submicron silicon powder is greater than or equal to 80%; C. The mass ratio of the product A to the carbonyl polymer is 3:0.5-3; D. The mass ratio of the product B to the phenolic resin alcohol solution is 1:5-20.
6. The method for preparing a core-shell submicron silicon-based negative electrode material according to claim 4, characterized in that: At least one of the following conditions is met: A. The vapor phase carbon deposition coating process comprises: introducing hydrogen and acetylene to react; B. The grinding time is 30min-120min; C. the grinding comprises ball milling; D. Before the second heating, the mixture obtained by the second mixing is allowed to stand.
7. The method for preparing a core-shell submicron silicon-based negative electrode material according to claim 6, characterized in that: At least one of the following conditions is met: A. The reaction time is 0.5h-2h; B. The gas flow rate of the hydrogen is 60mL / min-120mL / min; C. The gas flow rate of the acetylene is 10mL / min-30mL / min; D. The standing time is 1h-4h.
8. The method for preparing a core-shell submicron silicon-based negative electrode material according to any one of claims 4 to 7, characterized in that: At least one of the following conditions is met: A. The heating rate of the first heating is 3°C / min-6°C / min, and the heating end temperature is 900°C-1200°C; B. the second heating includes a third heating and a fourth heating performed sequentially; The third heating has a heating rate of 3°C / min-6°C / min, a heating end point temperature of 400°C-650°C, and a heating time of 1h-3h; The fourth heating has a heating rate of 3°C / min-6°C / min, a heating end point temperature of 900°C-1100°C, and a heating time of 3h-6h.
9. A lithium ion battery, characterized in that: A core-shell type submicron silicon-based negative electrode material comprising the core-shell type submicron silicon-based negative electrode material according to any one of claims 1 to 3 or a core-shell type submicron silicon-based negative electrode material prepared by the preparation method of the core-shell type submicron silicon-based negative electrode material according to any one of claims 4 to 8.
10. An electrical device, characterized in that: Includes the lithium ion battery as claimed in claim 9.